(untitled) (Research, Society and Development, 2020)
In the face of controversies about the treatment of tendon injuries, non-surgical treatment using photobiomodulation therapy has been shown to be effective in repair. Objective was to evaluate the effects of photobiomodulation therapy on the tendon repair process. 42 Rattus norvegicus belonging to the wistar lineage were used, which were randomly divided into 2 experimental groups: Control (CG); Photobiomodulation (PBM). The groups were subdivided into 3 experimental periods: 7, 14 and 21 days. PBM started 24 hours after injury induction and followed for 7, 14, 21 days. For FBM, the 660 nm, 40 mW, 0.23 J and 6 s laser was used. The volume of the edema was evaluated, immediately before the tendon transection; 24 hours later; on the day of euthanasia, following their respective experimental periods. Histopathological analysis of the region of the transect and the quantification of blood vessels were performed using HE. Edema results: 24 hours after injury induction, there was no statistical difference between the experimental groups. After the experimental periods, 7, 14 and 21 days, the PBM group was effective in reducing the edema compared to the control. Histological results revealed that the PBM group had a greater tendon injury compared to the control after 7 days. After 14 and 21 days, the PBM group showed a better repair process compared to the control group. Likewise, PBM showed a greater number of blood vessels when compared to the control, after all experimental periods. The PBM treatment was effective in reducing the volume of the edema, preventing degenerative morphological alterations of the tendon, after 21 days.